Effects of phase angle between the fretting load and the bulk load on the life of the AL7050 T7451 and ASTM 743 CA6NM - Gailliegue, Thomas (2018)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2018.